Subcutaneous calcium heparin versus intravenous sodium heparin in treatment of established acute deep vein thrombosis of the legs: a multicentre prospective randomised trial. Issue 6581 (9th May 1987) - Walker, M G; Shaw, J W; Thomson, G J; Cumming, J G; Thomas, M L
Abstract : One hundred patients with phlebographically proved acute deep vein thrombosis of the legs were prospectively randomised into two treatment groups to compare the safety and efficacy of subcutaneous calcium heparin versus intravenous sodium heparin administered by constant infusion pump. The dose of heparin was determined by daily measurement of the kaolin cephalin clotting time. Treatment was maintained for up to 14 days, after which phlebography was repeated. Of 49 patients who received subcutaneous calcium heparin, two showed an increase in thrombus size, while eight showed complete lysis. In the 47 patients who received intravenous sodium heparin thrombus increased in size in 13 while only one showed evidence of complete lysis. These differences were significant. There were no significant differences between the two groups in the incidence of serious complications, although almost half of those receiving intravenous heparin had some minor problem with the constant infusion pump and just over half of those receiving subcutaneous heparin had some bruising at the injection site. This study showed that subcutaneous calcium heparin was more effective in helping lyse existing thrombus and preventing its propagation than intravenous sodium heparin.